2016
DOI: 10.1111/acer.12936
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Prenatal Ethanol Exposure on Neuroanatomical and Behavioral Development in Mice

Abstract: Background In utero alcohol, or ethanol, exposure produces developmental abnormalities in the brain of the fetus, which can result in lifelong behavioral abnormalities. Fetal alcohol spectrum disorders (FASD) is a term used to describe a range of adverse developmental conditions caused by ethanol exposure during gestation. Children diagnosed with FASD potentially exhibit a host of phenotypes including growth retardation, facial dysmorphology, central nervous system anomalies, abnormal behavior and cognitive de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
40
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 52 publications
10
40
0
Order By: Relevance
“…It was later found that mice receiving the same paradigm exhibited altered patterning of spontaneous GABA-mediated synaptic barrages and increased GABA-mediated synaptic activity, while showing an increase in Cajal-Reizius cell numbers in cortical layer I (Skorput and Yeh 2015). Similar PAE-induced frontal cortex neuron abnormalities have been previously demonstrated in other mouse models implementing a chronic liquid diet for PAE, including the loss of GABAergic neurons in an acute 3rd trimester PAE paradigm (Skorput and Yeh 2015; Smiley et al 2015; Abbott et al 2016), in parallel with the altered neuronal circuitry seen in individuals with FASD (Rema and Ebner 1999; Sowell et al 2008). Importantly, at PN20 PAE, offspring show increased anxiety and impaired gross and fine motor coordination (El Shawa et al 2013).…”
Section: Mouse Models Of Prenatal Alcohol Exposuresupporting
confidence: 75%
See 2 more Smart Citations
“…It was later found that mice receiving the same paradigm exhibited altered patterning of spontaneous GABA-mediated synaptic barrages and increased GABA-mediated synaptic activity, while showing an increase in Cajal-Reizius cell numbers in cortical layer I (Skorput and Yeh 2015). Similar PAE-induced frontal cortex neuron abnormalities have been previously demonstrated in other mouse models implementing a chronic liquid diet for PAE, including the loss of GABAergic neurons in an acute 3rd trimester PAE paradigm (Skorput and Yeh 2015; Smiley et al 2015; Abbott et al 2016), in parallel with the altered neuronal circuitry seen in individuals with FASD (Rema and Ebner 1999; Sowell et al 2008). Importantly, at PN20 PAE, offspring show increased anxiety and impaired gross and fine motor coordination (El Shawa et al 2013).…”
Section: Mouse Models Of Prenatal Alcohol Exposuresupporting
confidence: 75%
“…Furthermore, the brain alterations seen tend to reflect changes in specific brain regions such as the olfactory bulbs, hippocampus, and cerebral cortex (Akers et al 2011; El Shawa et al 2013; Abbott et al 2016). Thus, the alterations produced by chronic first-to-second trimester PAE exposure may resemble the types of alterations observed in FASD, rather than the more severe craniofacial malformations normally observed in children with FASD with sentinel features (Chudley et al 2005; Cook et al 2016).…”
Section: Mouse Models Of Prenatal Alcohol Exposurementioning
confidence: 99%
See 1 more Smart Citation
“…Surprisingly, unlike the fetal brains, there were no differences in the cerebellar volumes of adolescent mice, suggesting a compensatory growth occurred during the late pre-natal, and/or post-natal periods. Post-natal structural recovery of several brain regions has been shown in a mouse model of alcohol exposure throughout pregnancy and, in that study, motor deficits were detected in the absence of concurrent structural defects (Abbott et al, 2016). As was suggested by those authors, structural defects that are apparent very early in development may be most predictive of later behavioral impairments.…”
Section: Discussionmentioning
confidence: 78%
“…Moreover, a previous study showed that pregnant guinea pigs can be successfully exposed to moderate ethanol concentrations using a 24-hour voluntary drinking paradigm, which is expected to be less stressful (Shea et al, 2012). It is also important to determine whether ethanol exposure during the equivalent to the first and second trimesters of human pregnancy (i.e., pregnancy in rodents; Clancy et al, 2007) also causes fetal brain micro-hemorrhages and whether these contribute to the morphological and functional alterations that have been detected in different brain regions, including the cerebral cortex (Kuhn and Miller, 1998, Climent et al, 2002, Fakoya and Caxton-Martins, 2006, El Shawa et al, 2013, Abbott et al, 2016). …”
Section: Discussionmentioning
confidence: 99%